A formula and process for preparing a light aluminum plate composite integrated plate by using industrial solid waste
Patent Information
- Application Number
- CN202610785748.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-30
AI Technical Summary
其一,依赖工业固废中过渡金属离子催化双氧水分解,因催化活性过强且缺乏调控手段,产气速率瞬间爆发,导致气泡合并、逃逸,引发爆泡与塌泡,孔隙结构杂乱无章;
本发明在低温段优先释放钙离子并与磷酸根生成磷酸钙微晶,同步钝化重金属;在中温段深度溶蚀释放硅、铝及过渡金属离子,形成富含活性前驱体的碱激发凝胶体系;随后,通过同源磷酸盐分阶段双重调控,对液相中过渡金属离子进行分阶段络合,使双氧水催化分解速率平稳可控,实现均匀发泡;以废玻璃为基体,经表面微溶蚀、磷酸钙锚定和硅铝酸盐凝胶包覆,制备出表面富含活性羟基的功能填料,替代外购商品化微珠填料,在气泡膨胀过程中架桥阻隔、构筑半封闭孔结构。最后,在热压梯度固化过程中,芯材无机凝胶与铝板表面羟基发生脱水缩合,生成化学键合界面,实现芯材与面板的一体化。
Smart Images

Figure CN123003247A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of industrial solid waste recycling technology, specifically to a formula and process for preparing lightweight aluminum composite integrated panels using industrial solid waste. Background Technology
[0002] Industrial solid waste refers to solid, semi-solid, and gaseous substances placed in containers that are generated during industrial production activities and have lost their original utilization value or have been discarded even if they have not lost their value. It mainly includes fly ash, steel slag, red mud, tailings, ceramic waste, etc., with an annual output of hundreds of millions of tons. If not disposed of properly, it will pose a serious threat to the ecological environment. Based on this, a process for preparing lightweight aluminum composite panels using industrial solid waste has emerged. The process uses lightweight inorganic materials made from industrial solid waste through special modification as the core layer. Through high-pressure composite, hot-press curing, and surface coating, the panel and core material are firmly combined into a composite panel that integrates decoration and thermal insulation. This realizes the high-value utilization of bulk solid waste and the synergistic preparation of green building materials.
[0003] Traditional processes have several drawbacks in the preparation of lightweight aluminum composite panels: Firstly, relying on transition metal ions in industrial solid waste to catalyze the decomposition of hydrogen peroxide results in excessively strong catalytic activity and a lack of control methods, leading to an instantaneous burst of gas production rate, causing bubbles to merge and escape, resulting in bursting and collapsing bubbles, and a chaotic pore structure. Secondly, the pore connectivity defect is prominent. After foaming, the bubble walls are thin and interconnected, forming open channels with a high water absorption rate. Water seeping into the core material can lead to freeze-thaw damage and failure of thermal insulation performance, resulting in a significant reduction in strength. Third, the interface bonding is weak. The core material and the aluminum plate rely on organic adhesive film for physical bonding, which lacks chemical bonding. It has poor weather resistance, is prone to aging and delamination, and the organic adhesive layer is flammable at high temperatures, which seriously restricts the fire safety and service life of the composite board.
[0004] Therefore, the present invention provides a formula and process for preparing lightweight aluminum composite integrated panels using industrial solid waste, in order to solve the related technical problems mentioned above. Summary of the Invention
[0005] The purpose of this invention is to provide a formula and process for preparing lightweight aluminum composite integrated panels using industrial solid waste. This involves utilizing the precipitation and complexation of transition metal ions by phosphate groups, precisely controlling catalytic activity in stages, and then reusing waste glass to prepare a functional filler. The filler's surface, after being coated with gel, is rich in active hydroxyl groups. This filler not only bridges and closes pores and reduces water absorption during foaming, but also participates in interfacial dehydration condensation reactions during hot pressing. This makes the foaming slurry itself a chemical bonding bridge connecting the core material and the aluminum plate, significantly improving interfacial peel strength. The resulting composite integrated panel core material is an entirely inorganic, non-combustible material, possessing comprehensive properties such as lightweight, heat insulation, fire resistance, and weather resistance.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, a formulation for preparing lightweight aluminum composite integrated panels using industrial solid waste is provided. The composite integrated panel formulation includes: multiple aluminum alloy thin plates and a foaming slurry, wherein the foaming slurry is disposed between the multiple aluminum alloy thin plates, and the foaming slurry includes: 95-105 parts of industrial solid waste, 13-17 parts of water glass, 15-18 parts of functional filler, 3.8-4.2 parts of hydrogen peroxide, and 40-50 parts of deionized water.
[0007] Furthermore, the preparation steps of the functional filler include: Waste glass is crushed into first and second particle sizes to obtain first glass powder and second glass powder respectively. The first glass powder and second glass powder are mixed in a mass ratio of 11-13:4-6 to obtain multi-stage glass powder. It should be added that the first particle size is 50–100 μm, and the second particle size is 20–45 μm; Multi-stage glass powder and sodium hydroxide solution were mixed at a mass ratio of 15-17:30-32, heated to 60-70℃, and stirred for 15-20 minutes. After stirring, the mixture was filtered and the filtered product was collected. The sodium hydroxide solution was 0.4 mol / L.
[0008] The filtered product was washed with deionized water and dried by forced air drying at 80–85°C for 1.8–2.2 h to obtain roughened glass powder. The roughened glass powder was dispersed in deionized water at a mass ratio of 1:1.1–1.3. Then, 0.4%–0.5% by mass of disodium hydrogen phosphate and 0.3%–0.4% by mass of calcium chloride were added to the roughened glass powder. After the addition was completed, the mixture was stirred at 23–25°C for 20–30 min. After stirring, the mixture was filtered to obtain deposited glass powder. The deposited glass powder was then coated to obtain a functional filler.
[0009] It should be noted that when washing with deionized water, the water must be washed until it is neutral.
[0010] Furthermore, the coating of the deposited glass powder specifically involves: Deposited glass powder, water glass, deionized water, and sodium aluminate were mixed in a mass ratio of 16–18:2.5–3.5:8–12:0.02–0.04, heated to 58–62°C, and stirred for 0.8–1.2 h. After stirring, the mixture was filtered, washed with deionized water, and dried at 80–85°C for 1.8–2.2 h to obtain the functional filler.
[0011] A process for preparing lightweight aluminum composite panels using industrial solid waste, the process comprising: Industrial solid waste is activated in multiple stages to form an activated slurry. The activated slurry is then cooled and metal ion regulation is performed to obtain a pre-cooled slurry. The industrial solid waste includes steel slag, fly ash, and red mud; Waste glass is pretreated to prepare functional fillers, and foaming operations are performed using the functional fillers to obtain foamed slurry. Multiple aluminum alloy sheets are pretreated, foaming slurry is poured into one of the pretreated aluminum alloy sheets, and then another pretreated aluminum alloy sheet is used to cover it. Gradual curing is carried out by hot press, and the composite aluminum sheet is demolded. The composite aluminum plate is left to stand for a period of time for curing. After the curing period, the composite aluminum plate is dried, and then the edges are trimmed and sealed to obtain a composite integrated plate.
[0012] Furthermore, the multi-stage activation of industrial solid waste includes: Steel slag, fly ash, and red mud are mixed in a mass ratio of 2–2.5:3–3.5:1 and stirred for 20–30 minutes to obtain mixed solid waste. Mix solid waste, water glass, and deionized water in a mass ratio of 6-7:1:2-3, and add sodium dihydrogen phosphate at a mass ratio of 0.9%-1.1% of water glass. Heat to 45-55°C and stir for 1.5-2 hours to obtain the first slurry. Sodium dihydrogen phosphate, after dissolving, provides phosphate ions that react with calcium ions in the first slurry to form calcium phosphate microcrystals, which are then uniformly dispersed in the first slurry.
[0013] After obtaining the first slurry, the temperature is raised to 75-85℃ and stirring is continued for 1.5-2 hours. After stirring is completed, the activated slurry is obtained, and the pH value of the activated slurry is 12-13.
[0014] Furthermore, the obtained pre-cooled slurry specifically includes: Cool the activated slurry to 25-35°C, add 0.06%-0.13% by mass of disodium hydrogen phosphate to the activated slurry, and stir until completely dissolved to obtain a pre-cooled slurry.
[0015] The disodium hydrogen phosphate and the sodium dihydrogen phosphate from the previous step form a dual-stage regulation system of homologous phosphates, ensuring a stable and controllable foaming rate and preventing bursting of foam.
[0016] Once the functional filler is prepared, it must be stored in a dry and sealed condition and used within 24 hours.
[0017] Furthermore, the obtained foaming slurry includes: Add 15%–20% functional filler (by mass of mixed solid waste) to the pre-cooled slurry, stir for 3–5 minutes, add 30% hydrogen peroxide (by mass) during stirring, stir for 15–20 seconds, then transfer to a mold for pouring to obtain foamed slurry.
[0018] In addition, the amount of hydrogen peroxide with a mass fraction of 30% is added at 22% to 24% of the mass of the functional filler. To prevent the functional filler from settling due to its high density, the amount of water glass can be finely adjusted to increase the viscosity of the slurry.
[0019] Furthermore, the pretreatment of multiple aluminum alloy sheets includes: Multiple aluminum alloy sheets were immersed in a 5% sodium hydroxide solution at 45–50°C for 40–50 seconds. After immersion, they were immersed in a 2% nitric acid solution for 8–12 seconds and then removed and washed with deionized water.
[0020] The foaming slurry is poured onto one of the pretreated aluminum alloy sheets, and then covered with another pretreated aluminum alloy sheet, ensuring that the hydroxyl side of both pretreated aluminum alloy sheets is in contact with the foaming slurry. Furthermore, the gradient curing process using a hot press is specifically carried out as follows: Heat to 58–60°C, apply pressure of 0.2–0.3 MPa, hold for 25–30 minutes, continue heating to 120–125°C, increase pressure to 0.8–1.0 MPa, hold for 60–70 minutes, further heat to 150–155°C, hold for 60–70 minutes.
[0021] Furthermore, the process of allowing the composite aluminum plate to stand for a period of time for curing specifically involves placing the composite aluminum plate in an environment with a relative humidity of 60% to 80% and a temperature of 23 to 25°C for 36 to 48 hours.
[0022] After the settling period, the composite aluminum plate is dried, and then the edges are trimmed and sealed. Specifically: The composite aluminum plate is transferred into a forced-air drying oven and dried at 70℃ for 6 hours to remove residual free water, stabilize the dimensions, cut the plate according to specifications, and fold the edges of the aluminum plate to completely cover the core material and isolate it from environmental moisture, thus obtaining a composite integrated plate.
[0023] Compared with the prior art, the beneficial effects of the present invention are: This invention preferentially releases calcium ions at low temperatures, which then react with phosphate ions to form calcium phosphate microcrystals, simultaneously passivating heavy metals. At mid-temperature temperatures, deep etching releases silicon, aluminum, and transition metal ions, forming an alkali-activated gel system rich in active precursors. Subsequently, through staged dual regulation using homologous phosphates, transition metal ions in the liquid phase are complexed in stages, ensuring a stable and controllable hydrogen peroxide catalytic decomposition rate and achieving uniform foaming. Using waste glass as a matrix, a functional filler rich in active hydroxyl groups is prepared through surface micro-etching, calcium phosphate anchoring, and aluminosilicate gel coating. This filler replaces commercially available microsphere fillers, bridging and blocking during bubble expansion and constructing a semi-closed pore structure. Finally, during hot-press gradient curing, the inorganic gel of the core material undergoes dehydration condensation with the hydroxyl groups on the aluminum plate surface, generating a chemically bonded interface and achieving integration of the core material and the panel.
[0024] This process utilizes the precipitation and complexation of transition metal ions by phosphate groups to precisely control catalytic activity in stages. Waste glass is then reused to prepare functional fillers. After being coated with gel, the fillers are rich in active hydroxyl groups, which not only bridge and close pores and reduce water absorption during foaming, but also participate in interfacial dehydration condensation reactions during hot pressing. This makes the foaming slurry itself a chemical bonding bridge connecting the core material and the aluminum plate, significantly improving the interfacial peel strength. The resulting composite integrated board core material is an all-inorganic non-combustible material with comprehensive properties such as lightweight, heat insulation, fire resistance, and weather resistance. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a flowchart of a process for preparing lightweight aluminum composite integrated panels using industrial solid waste, according to the present invention. Detailed Implementation
[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] In this embodiment, the water glass is liquid sodium silicate with a modulus of 2.0, and the aluminum alloy sheet is 3003 aluminum alloy with a thickness of 0.8 mm.
[0029] Example 1
[0030] like Figure 1 As shown, a formulation for preparing lightweight aluminum composite integrated panels using industrial solid waste is disclosed. The formulation comprises: multiple aluminum alloy thin plates and foaming slurry, wherein the foaming slurry is disposed between the multiple aluminum alloy thin plates and comprises: 95 parts industrial solid waste, 13 parts water glass, 15 parts functional filler, 3.8 parts hydrogen peroxide, and 40 parts deionized water.
[0031] Furthermore, the preparation steps of the functional filler include: Waste glass is crushed into first and second particle sizes to obtain first glass powder and second glass powder respectively. The first glass powder and second glass powder are mixed in a mass ratio of 11:4 to obtain multi-stage glass powder. Multi-stage glass powder and sodium hydroxide solution were mixed at a mass ratio of 15:30, heated to 60℃, stirred for 15 minutes, filtered after stirring, and the filtered product was collected. The sodium hydroxide solution was 0.4 mol / L.
[0032] The filtered product was washed with deionized water and dried at 80°C for 1.8 hours to obtain roughened glass powder. The roughened glass powder was dispersed in deionized water at a mass ratio of 1:1.1. Then, 0.4% by mass of disodium hydrogen phosphate and 0.3% by mass of calcium chloride were added to the roughened glass powder. After the addition was completed, the mixture was stirred at 23°C for 20 minutes. After stirring, the mixture was filtered to obtain deposited glass powder. The deposited glass powder was then coated to obtain a functional filler.
[0033] It should be noted that when washing with deionized water, the water must be washed until it is neutral.
[0034] Furthermore, the coating of the deposited glass powder specifically involves: Deposited glass powder, water glass, deionized water, and sodium aluminate were mixed in a mass ratio of 16:2.5:8:0.02, heated to 58°C, and stirred for 0.8 hours. After stirring, the mixture was filtered, washed with deionized water, and dried at 80°C for 1.8 hours to obtain the functional filler.
[0035] Once the functional filler is prepared, it must be stored in a dry and sealed condition and used within 24 hours.
[0036] A process for preparing lightweight aluminum composite panels using industrial solid waste, the process comprising: Industrial solid waste is activated in multiple stages to form an activated slurry. The activated slurry is then cooled and metal ion regulation is performed to obtain a pre-cooled slurry. The industrial solid waste includes steel slag, fly ash, and red mud; Waste glass is pretreated to prepare functional fillers, and foaming operations are performed using the functional fillers to obtain foamed slurry. Multiple aluminum alloy sheets are pretreated, foaming slurry is poured into one of the pretreated aluminum alloy sheets, and then another pretreated aluminum alloy sheet is used to cover it. Gradual curing is carried out by hot press, and the composite aluminum sheet is demolded. The composite aluminum plate is left to stand for a period of time for curing. After the curing period, the composite aluminum plate is dried, and then the edges are trimmed and sealed to obtain a composite integrated plate.
[0037] Furthermore, the multi-stage activation of industrial solid waste includes: Steel slag, fly ash and red mud were mixed in a mass ratio of 2:3:1 and stirred for 20 minutes to obtain mixed solid waste. Mix solid waste, water glass, and deionized water in a mass ratio of 6:1:2, add sodium dihydrogen phosphate at a mass of 0.9% of water glass, heat to 45°C, and stir for 1.5 hours to obtain the first slurry. Sodium dihydrogen phosphate, after dissolving, provides phosphate ions that react with calcium ions in the first slurry to form calcium phosphate microcrystals, which are then uniformly dispersed in the first slurry.
[0038] After obtaining the first slurry, the temperature is raised to 75°C and stirring is continued for 1.5 hours. After stirring is completed, the activated slurry is obtained.
[0039] Furthermore, the obtained pre-cooled slurry specifically includes: Cool the activated slurry to 25°C, add 0.06% by mass of disodium hydrogen phosphate to the activated slurry, and stir until completely dissolved to obtain a pre-cooled slurry.
[0040] Furthermore, the obtained foaming slurry includes: Add functional filler of 15% by mass of mixed solid waste to the pre-cooled slurry, stir for 3 minutes, add hydrogen peroxide of 30% by mass during the stirring process, stir for 15 seconds, transfer to mold for pouring, and obtain foamed slurry.
[0041] In addition, the hydrogen peroxide with a mass fraction of 30% is added at 22% of the mass of the functional filler. To prevent the functional filler from settling due to its high density, the amount of water glass can be finely adjusted to increase the viscosity of the slurry.
[0042] Furthermore, the pretreatment of multiple aluminum alloy sheets includes: Multiple aluminum alloy sheets were immersed in a 5% sodium hydroxide solution at 45°C for 40 seconds. After immersion, they were immersed in a 2% nitric acid solution for 8 seconds and then removed. After removal, they were washed with deionized water.
[0043] The foaming slurry is poured onto one of the pretreated aluminum alloy sheets, and then covered with another pretreated aluminum alloy sheet, ensuring that the hydroxyl side of both pretreated aluminum alloy sheets is in contact with the foaming slurry. Furthermore, the gradient curing process using a hot press is specifically carried out as follows: Heat to 58℃, apply a pressure of 0.2MPa, hold for 25 minutes, continue heating to 120℃, increase the pressure to 0.80MPa, hold for 60 minutes, further heat to 150℃, hold for 60 minutes.
[0044] Furthermore, the process of allowing the composite aluminum plate to stand for a period of time for curing specifically involves placing the composite aluminum plate in an environment with 60% relative humidity and 23°C for 36 hours.
[0045] After the settling period, the composite aluminum plate is dried, and then the edges are trimmed and sealed. Specifically: The composite aluminum plate is transferred into a forced-air drying oven and dried at 70℃ for 6 hours to remove residual free water, stabilize the dimensions, cut the plate according to specifications, and fold the edges of the aluminum plate to completely cover the core material and isolate it from environmental moisture, thus obtaining a composite integrated plate.
[0046] Example 2
[0047] The process for preparing lightweight aluminum composite integrated panels using industrial solid waste provided in this embodiment is basically the same as that in Embodiment 1. The main difference between the two lies in the specific composition and ratio of the raw materials used. In this embodiment, a formula for preparing lightweight aluminum composite integrated panels using industrial solid waste is provided. The composite integrated panel formula includes: multiple aluminum alloy thin plates and foaming slurry. The foaming slurry is disposed between the multiple aluminum alloy thin plates. The foaming slurry includes: 105 parts of industrial solid waste, 17 parts of water glass, 18 parts of functional filler, 4.2 parts of hydrogen peroxide, and 50 parts of deionized water.
[0048] Furthermore, the preparation steps of the functional filler include: Waste glass is crushed into first and second particle sizes to obtain first glass powder and second glass powder respectively. The first glass powder and second glass powder are mixed in a mass ratio of 13:6 to obtain multi-stage glass powder. Multi-stage glass powder and sodium hydroxide solution were mixed at a mass ratio of 17:32, heated to 70°C, stirred for 20 minutes, filtered after stirring, and the filtered product was collected. The sodium hydroxide solution was 0.4 mol / L.
[0049] The filtered product was washed with deionized water and dried at 85°C for 2.2 hours to obtain roughened glass powder. The roughened glass powder was dispersed in deionized water at a mass ratio of 1:1.3. Then, 0.5% by mass of disodium hydrogen phosphate and 0.4% by mass of calcium chloride were added to the roughened glass powder. After the addition was completed, the mixture was stirred at 25°C for 30 minutes. After stirring, the mixture was filtered to obtain deposited glass powder. The deposited glass powder was then coated to obtain a functional filler.
[0050] It should be noted that when washing with deionized water, the water must be washed until it is neutral.
[0051] Furthermore, the coating of the deposited glass powder specifically involves: Deposited glass powder, water glass, deionized water, and sodium aluminate were mixed in a mass ratio of 18:3.5:12:0.04, heated to 62°C, and stirred for 1.2 hours. After stirring, the mixture was filtered, washed with deionized water, and dried at 85°C for 2.2 hours to obtain the functional filler.
[0052] Once the functional filler is prepared, it must be stored in a dry and sealed condition and used within 24 hours.
[0053] A process for preparing lightweight aluminum composite panels using industrial solid waste, the process comprising: Industrial solid waste is activated in multiple stages to form an activated slurry. The activated slurry is then cooled and metal ion regulation is performed to obtain a pre-cooled slurry. The industrial solid waste includes steel slag, fly ash, and red mud; Waste glass is pretreated to prepare functional fillers, and foaming operations are performed using the functional fillers to obtain foamed slurry. Multiple aluminum alloy sheets are pretreated, foaming slurry is poured into one of the pretreated aluminum alloy sheets, and then another pretreated aluminum alloy sheet is used to cover it. Gradual curing is carried out by hot press, and the composite aluminum sheet is demolded. The composite aluminum plate is left to stand for a period of time for curing. After the curing period, the composite aluminum plate is dried, and then the edges are trimmed and sealed to obtain a composite integrated plate.
[0054] Furthermore, the multi-stage activation of industrial solid waste includes: Steel slag, fly ash, and red mud were mixed in a mass ratio of 2.5:3.5:1 and stirred for 30 minutes to obtain mixed solid waste. Mix solid waste, water glass, and deionized water in a mass ratio of 7:1:3, add sodium dihydrogen phosphate at a mass of 1.1% of water glass, heat to 55°C, and stir for 2 hours to obtain the first slurry. Sodium dihydrogen phosphate, after dissolving, provides phosphate ions that react with calcium ions in the first slurry to form calcium phosphate microcrystals, which are then uniformly dispersed in the first slurry.
[0055] After obtaining the first slurry, the temperature is raised to 85℃ and stirring is continued for 2 hours. After stirring is completed, the activated slurry is obtained.
[0056] Furthermore, the obtained pre-cooled slurry specifically includes: Cool the activated slurry to 35°C, add 0.13% by mass of disodium hydrogen phosphate to the activated slurry, and stir until completely dissolved to obtain a pre-cooled slurry.
[0057] Furthermore, the obtained foaming slurry includes: Add 20% functional filler (by mass of mixed solid waste) to the pre-cooled slurry, stir for 5 minutes, add 30% hydrogen peroxide (by mass) during stirring, stir for 20 seconds, then transfer to a mold for pouring to obtain foamed slurry.
[0058] In addition, the hydrogen peroxide with a mass fraction of 30% is added at 24% of the mass of the functional filler. To prevent the functional filler from settling due to its high density, the amount of water glass can be finely adjusted to increase the viscosity of the slurry.
[0059] Furthermore, the pretreatment of multiple aluminum alloy sheets includes: Multiple aluminum alloy sheets were immersed in a 5% sodium hydroxide solution at 50°C for 50 seconds. After immersion, they were immersed in a 2% nitric acid solution for 12 seconds and then removed. After removal, they were washed with deionized water.
[0060] The foaming slurry is poured onto one of the pretreated aluminum alloy sheets, and then covered with another pretreated aluminum alloy sheet, ensuring that the hydroxyl side of both pretreated aluminum alloy sheets is in contact with the foaming slurry. Furthermore, the gradient curing process using a hot press is specifically carried out as follows: Heat to 60℃, apply a pressure of 0.3MPa, hold for 30 minutes, continue heating to 125℃, increase the pressure to 1.0MPa, hold for 70 minutes, further heat to 155℃, hold for 70 minutes.
[0061] Furthermore, the process of allowing the composite aluminum plate to stand for a period of time for curing specifically involves placing the composite aluminum plate in an environment with 80% relative humidity and 25°C for 48 hours.
[0062] After the settling period, the composite aluminum plate is dried, and then the edges are trimmed and sealed. Specifically: The composite aluminum plate is transferred into a forced-air drying oven and dried at 70℃ for 6 hours to remove residual free water, stabilize the dimensions, cut the plate according to specifications, and fold the edges of the aluminum plate to completely cover the core material and isolate it from environmental moisture, thus obtaining a composite integrated plate.
[0063] Example 3
[0064] The process for preparing lightweight aluminum composite integrated panels using industrial solid waste provided in this embodiment is basically the same as that in Embodiment 1. The main difference between the two lies in the specific composition and ratio of the raw materials used. In this embodiment, a formula for preparing lightweight aluminum composite integrated panels using industrial solid waste is provided. The composite integrated panel formula includes: multiple aluminum alloy thin plates and foaming slurry. The foaming slurry is disposed between the multiple aluminum alloy thin plates. The foaming slurry includes: 100 parts of industrial solid waste, 15 parts of water glass, 17 parts of functional filler, 4 parts of hydrogen peroxide, and 45 parts of deionized water.
[0065] Furthermore, the preparation steps of the functional filler include: Waste glass is crushed into first and second particle sizes to obtain first glass powder and second glass powder respectively. The first glass powder and second glass powder are mixed in a mass ratio of 12:5 to obtain multi-stage glass powder. Multi-stage glass powder and sodium hydroxide solution were mixed at a mass ratio of 16:31, heated to 65°C, and stirred for 18 minutes. After stirring, the mixture was filtered, and the filtered product was collected. The sodium hydroxide solution was 0.4 mol / L.
[0066] The filtered product was washed with deionized water and dried at 83℃ for 2 hours to obtain roughened glass powder. The roughened glass powder was dispersed in deionized water at a mass ratio of 1:1.2. Then, 0.4% to 0.5% by mass of disodium hydrogen phosphate and 0.35% by mass of calcium chloride were added to the roughened glass powder. After the addition was completed, the mixture was stirred at 24℃ for 25 minutes. After stirring, the mixture was filtered to obtain deposited glass powder. The deposited glass powder was then coated to obtain a functional filler.
[0067] It should be noted that when washing with deionized water, the water must be washed until it is neutral.
[0068] Furthermore, the coating of the deposited glass powder specifically involves: Deposited glass powder, water glass, deionized water, and sodium aluminate were mixed in a mass ratio of 17:3:10:0.03, heated to 60°C and stirred for 1 hour. After stirring, the mixture was filtered, washed with deionized water, and dried at 83°C for 2 hours to obtain the functional filler.
[0069] Once the functional filler is prepared, it must be stored in a dry and sealed condition and used within 24 hours.
[0070] A process for preparing lightweight aluminum composite panels using industrial solid waste, the process comprising: Industrial solid waste is activated in multiple stages to form an activated slurry. The activated slurry is then cooled and metal ion regulation is performed to obtain a pre-cooled slurry. The industrial solid waste includes steel slag, fly ash, and red mud; Waste glass is pretreated to prepare functional fillers, and foaming operations are performed using the functional fillers to obtain foamed slurry. Multiple aluminum alloy sheets are pretreated, foaming slurry is poured into one of the pretreated aluminum alloy sheets, and then another pretreated aluminum alloy sheet is used to cover it. Gradual curing is carried out by hot press, and the composite aluminum sheet is demolded. The composite aluminum plate is left to stand for a period of time for curing. After the curing period, the composite aluminum plate is dried, and then the edges are trimmed and sealed to obtain a composite integrated plate.
[0071] Furthermore, the multi-stage activation of industrial solid waste includes: Steel slag, fly ash, and red mud were mixed in a mass ratio of 2.3:3.3:1 and stirred for 25 minutes to obtain mixed solid waste. Mixed solid waste, water glass, and deionized water in a mass ratio of 6.5:1:2.5, and sodium dihydrogen phosphate at 1% of the mass of water glass is added. The mixture is heated to 50°C and stirred for 1.8 hours to obtain the first slurry. Sodium dihydrogen phosphate, after dissolving, provides phosphate ions that react with calcium ions in the first slurry to form calcium phosphate microcrystals, which are then uniformly dispersed in the first slurry.
[0072] After obtaining the first slurry, the temperature is raised to 80℃ and stirring is continued for 1.8 hours. After stirring is completed, the activated slurry is obtained.
[0073] Furthermore, the obtained pre-cooled slurry specifically includes: Cool the activated slurry to 30°C, add 0.09% by mass of disodium hydrogen phosphate to the activated slurry, and stir until completely dissolved to obtain a pre-cooled slurry.
[0074] Furthermore, the obtained foaming slurry includes: Add functional filler of 18% by mass of mixed solid waste to the pre-cooled slurry, stir for 4 minutes, add hydrogen peroxide of 30% by mass during the stirring process, stir for 18 seconds, transfer to mold for pouring, and obtain foamed slurry.
[0075] In addition, the hydrogen peroxide with a mass fraction of 30% is added at 23% of the mass of the functional filler. To prevent the functional filler from settling due to its high density, the amount of water glass can be finely adjusted to increase the viscosity of the slurry.
[0076] Furthermore, the pretreatment of multiple aluminum alloy sheets includes: Multiple aluminum alloy sheets were immersed in a 5% sodium hydroxide solution at 48°C for 45 seconds. After immersion, they were immersed in a 2% nitric acid solution for 10 seconds and then removed. After removal, they were washed with deionized water.
[0077] The foaming slurry is poured onto one of the pretreated aluminum alloy sheets, and then covered with another pretreated aluminum alloy sheet, ensuring that the hydroxyl side of both pretreated aluminum alloy sheets is in contact with the foaming slurry. Furthermore, the gradient curing process using a hot press is specifically carried out as follows: Heat to 59℃, apply a pressure of 0.25MPa, hold for 28 minutes, continue heating to 123℃, increase the pressure to 0.9MPa, hold for 65 minutes, further heat to 153℃, hold for 65 minutes.
[0078] Furthermore, the process of allowing the composite aluminum plate to stand for a period of time for curing specifically involves placing the composite aluminum plate in an environment with 70% relative humidity and 24°C for 42 hours.
[0079] After the settling period, the composite aluminum plate is dried, and then the edges are trimmed and sealed. Specifically: The composite aluminum plate is transferred into a forced-air drying oven and dried at 70℃ for 6 hours to remove residual free water, stabilize the dimensions, cut the plate according to specifications, and fold the edges of the aluminum plate to completely cover the core material and isolate it from environmental moisture, thus obtaining a composite integrated plate.
[0080] Comparative Example 1: The specific proportions of the raw materials for the process of preparing lightweight aluminum composite integrated panels using industrial solid waste provided in this embodiment are roughly the same as those in Example 1. The main difference is that an equal amount of multi-stage glass powder is used to replace the functional filler in this embodiment.
[0081] Comparative Example 2: The specific proportions of the raw materials and the process for preparing lightweight aluminum composite integrated panels using industrial solid waste provided in this embodiment are roughly the same as those in Example 1. The main difference is that in this embodiment, an equal amount of the first slurry is used instead of the activation slurry.
[0082] Comparative Example 3: The specific proportions of the raw materials and the process for preparing lightweight aluminum composite integrated panels using industrial solid waste provided in this example are roughly the same as those in Example 1. The main difference is that the dual regulation of phosphate is cancelled in this example, that is, no disodium hydrogen phosphate is added.
[0083] Effect test The composite integrated plate raw materials prepared by Examples 1 to 3 of the present invention are respectively designated as Experimental Examples 1 to 3; the composite integrated plate raw materials prepared by Comparative Examples 1 to 3 are respectively designated as Comparative Examples 1 to 3; and then the performance of each group of composite integrated plate raw materials in equal amounts is tested.
[0084] Experimental setup: Mechanical property testing: Test criteria: The bending strength of the overall composite panel was tested according to national standard GB / T 17748-2016 "Aluminum Composite Panels for Building Curtain Walls"; the compressive strength of the core material was tested according to national standard GB / T 5486-2008 "Test Methods for Inorganic Rigid Thermal Insulation Products". Each sample was tested three times, and the average value was taken as the final result. The test environment was 23℃ and 60% relative humidity. The experimental results are detailed in Table 1. Table 1: Mechanical Properties
[0085] The mechanical properties of Examples 1-3 are significantly better than those of the comparative examples, with Example 2 being the best. Comparative Example 1 exhibits poor slurry bonding, resulting in decreased mechanical properties; Comparative Example 2 shows insufficient activation of industrial solid waste, leading to ion bursting, uneven foaming, and a loose core structure, resulting in the worst mechanical properties; Comparative Example 3 exhibits bursting bubbles and interconnected cells, affecting structural stability, exhibiting poor compatibility, and weak interfacial bonding; Examples 1-3, through reasonable proportioning and a complete process, show a tight bond between the core material and the aluminum plate, resulting in a stable structure and meeting mechanical property standards.
[0086] Thermal insulation performance test: Test basis: Referencing national standard GB / T 10294-2008 "Determination of Steady-State Thermal Resistance and Related Properties of Thermal Insulation Materials - Protective Hot Plate Method", the test item was thermal conductivity. Each sample was tested three times, and the average value was taken. The test temperature was 25℃. Core material density and water absorption were tested simultaneously. The data results are shown in Table 2. Table 2: Thermal Insulation Performance Table
[0087] Example 2 exhibits the lowest thermal conductivity and water absorption, resulting in optimal insulation and closed-cell performance. Comparative Example 1 shows uneven cell structure and high connectivity, leading to increased water absorption and decreased insulation performance. Comparative Example 2 suffers from an unreasonable core material pore structure, high water absorption, accelerated heat conduction, and poor insulation performance. Comparative Example 3 exhibits poor insulation and closed-cell performance due to bursting and interconnected cells. The examples demonstrate how functional filler modification and a complete process can create uniform closed cells, effectively blocking heat transfer.
[0088] Aluminum sheet-core peel strength test: Test Basis: The peel strength test method was based on the national standard GB / T 17748-2016 "Aluminum Composite Panels for Building Curtain Walls". The test method was the tensile peel method. Each sample was tested three times, and the average value was taken. The test speed was 5 mm / min, and the test environment was 23℃ and 60% relative humidity. See Table 3 for details. Table 3: Peel Strength Table
[0089] The peel strength of the aluminum plate-core material in the examples was higher than that in the comparative examples, with Example 2 showing the highest peel strength and the tightest bond between the core material and the aluminum plate. In Comparative Example 1, the functional filler had insufficient adhesion to the core material and aluminum plate, resulting in low peel strength; in Comparative Example 2, the slurry activity was insufficient, leading to weak bonding with the hydroxyl groups on the aluminum plate surface, resulting in the lowest peel strength; in Comparative Example 3, uneven foaming resulted in weak interfacial bonding and poor peel strength. The examples, through aluminum plate pretreatment and functional filler modification, enhanced the interfacial bonding between the core material and the aluminum plate, exhibiting excellent peel strength.
[0090] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0091] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A formula for preparing lightweight aluminum composite integrated panels using industrial solid waste, characterized in that, The composite integrated panel formula includes: multiple aluminum alloy thin plates and foaming slurry, wherein the foaming slurry is disposed between the multiple aluminum alloy thin plates, and the foaming slurry includes: 95-105 parts industrial solid waste, 13-17 parts water glass, 15-18 parts functional filler, 3.8-4.2 parts hydrogen peroxide and 40-50 parts deionized water.
2. The formulation for preparing lightweight aluminum composite integrated panels using industrial solid waste according to claim 1, characterized in that, The preparation steps of the functional filler include: Waste glass is crushed into first and second particle sizes to obtain first glass powder and second glass powder respectively. The first glass powder and second glass powder are mixed in a mass ratio of 11-13:4-6 to obtain multi-stage glass powder. Mix multi-stage glass powder with sodium hydroxide solution at a mass ratio of 15-17:30-32, heat to 60-70℃, stir for 15-20 minutes, filter after stirring, and collect the filtered product. The filtered product was washed with deionized water and dried by forced air drying at 80–85°C for 1.8–2.2 h to obtain roughened glass powder. The roughened glass powder was dispersed in deionized water at a mass ratio of 1:1.1–1.
3. Then, 0.4%–0.5% by mass of disodium hydrogen phosphate and 0.3%–0.4% by mass of calcium chloride were added to the roughened glass powder. After the addition was completed, the mixture was stirred at 23–25°C for 20–30 min. After stirring, the mixture was filtered to obtain deposited glass powder. The deposited glass powder was then coated to obtain a functional filler.
3. The formulation for preparing lightweight aluminum composite integrated panels using industrial solid waste according to claim 2, characterized in that, The coating of the deposited glass powder specifically involves: Deposited glass powder, water glass, deionized water, and sodium aluminate were mixed in a mass ratio of 16–18:2.5–3.5:8–12:0.02–0.04, heated to 58–62°C, and stirred for 0.8–1.2 h. After stirring, the mixture was filtered, washed with deionized water, and dried at 80–85°C for 1.8–2.2 h to obtain the functional filler.
4. The process for preparing lightweight aluminum composite integrated panels using industrial solid waste according to any one of claims 1 to 3, characterized in that: The process includes: Industrial solid waste is activated in multiple stages to form an activated slurry. The activated slurry is then cooled and metal ion regulation is performed to obtain a pre-cooled slurry. The industrial solid waste includes steel slag, fly ash, and red mud; Waste glass is pretreated to prepare functional fillers, and foaming operations are performed using the functional fillers to obtain foamed slurry. Multiple aluminum alloy sheets are pretreated, foaming slurry is poured into one of the pretreated aluminum alloy sheets, and then another pretreated aluminum alloy sheet is used to cover it. Gradual curing is carried out by hot press, and the composite aluminum sheet is demolded. The composite aluminum plate is left to stand for a period of time for curing. After the curing period, the composite aluminum plate is dried, and then the edges are trimmed and sealed to obtain a composite integrated plate.
5. The process for preparing lightweight aluminum composite integrated panels using industrial solid waste according to claim 4, characterized in that: The multi-stage activation of industrial solid waste includes: Steel slag, fly ash, and red mud are mixed in a mass ratio of 2–2.5:3–3.5:1 and stirred for 20–30 minutes to obtain mixed solid waste. Mix solid waste, water glass, and deionized water in a mass ratio of 6-7:1:2-3, and add sodium dihydrogen phosphate at a mass ratio of 0.9%-1.1% of water glass. Heat to 45-55°C and stir for 1.5-2 hours to obtain the first slurry. After obtaining the first slurry, the temperature is raised to 75-85℃ and stirring is continued for 1.5-2 hours. After stirring is completed, the activated slurry is obtained.
6. The process for preparing lightweight aluminum composite integrated panels using industrial solid waste according to claim 5, characterized in that: The pre-cooled slurry obtained is specifically as follows: Cool the activated slurry to 25-35°C, add 0.06%-0.13% by mass of disodium hydrogen phosphate to the activated slurry, and stir until completely dissolved to obtain a pre-cooled slurry.
7. The process for preparing lightweight aluminum composite integrated panels using industrial solid waste according to claim 4, characterized in that: The obtained foamed slurry includes: Add 15%–20% functional filler (by mass of mixed solid waste) to the pre-cooled slurry, stir for 3–5 minutes, add 30% hydrogen peroxide (by mass) during stirring, stir for 15–20 seconds, then transfer to a mold for pouring to obtain foamed slurry.
8. The process for preparing lightweight aluminum composite integrated panels using industrial solid waste according to claim 4, characterized in that: The pretreatment of multiple aluminum alloy sheets includes: Multiple aluminum alloy sheets were immersed in a 5% sodium hydroxide solution at 45–50°C for 40–50 seconds. After immersion, they were immersed in a 2% nitric acid solution for 8–12 seconds and then removed and washed with deionized water.
9. The process for preparing lightweight aluminum composite integrated panels using industrial solid waste according to claim 8, characterized in that: The gradient curing process using a hot press is performed as follows: Heat to 58-60℃, apply pressure of 0.2-0.3MPa, hold for 25-30 minutes, continue heating to 120-125℃, increase pressure to 0.8-1.0MPa, hold for 60-70 minutes, further heat to 150-155℃, hold for 60-70 minutes; The process of allowing the composite aluminum plate to stand still for a period of time for curing specifically involves placing the composite aluminum plate in an environment with a relative humidity of 60% to 80% and a temperature of 23 to 25°C for 36 to 48 hours.